2004
DOI: 10.1111/j.1365-2273.2004.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Is acoustic analysis of snoring an alternative to sleep nasendoscopy?

Abstract: Previous studies have suggested that acoustic analysis may be useful in distinguishing different types of snoring prior to possible corrective surgery. This study aimed to establish whether it could replace sleep nasendoscopy in a clinical setting. Thirty-five patients undergoing sleep nasendoscopy had their snoring recorded and analysed using commercially available equipment. It was found that centre frequency can be used to distinguish pure palatal from tongue base snoring, with a clear cut-off value of 90 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 9 publications
1
29
2
1
Order By: Relevance
“…Thereby, a possible differentiation between palatal and non-palatal snoring is frequently reported. Contrary to that, other sites of obstruction can hardly be detected by acoustic analyses [4,1,7,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Thereby, a possible differentiation between palatal and non-palatal snoring is frequently reported. Contrary to that, other sites of obstruction can hardly be detected by acoustic analyses [4,1,7,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 64%
“…In recent years, various publications differentiate specific snoring types and anatomic structures that may create specific snoring sounds. Tongue base snoring is reported to have predominant frequency patterns above 500 Hz and palatinal snoring below 500 Hz [3,4,1,2,[5][6][7][8]. Most data are based on the visualisation of vibrating structures during sleep endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high cost of PSG and the high prevalence of OSA in the general population have persuaded researchers to look for portable monitoring devices, such as acoustic techniques, for sleep apnea monitoring [5,6,[19][20][21][22]. However, the previous studies on flow-sound relationship were all focused on data of awake non-OSA individuals.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies, including those by the senior author, have described the use of acoustic analysis to predict the site of upper airway obstruction in snoring patients. For example, Saunders et al [4] identified that palatal snorers produced sound with a centre frequency below 90 Hz, whereas all pure tongue-base snorers produced sound with a centre frequency above this value, thereby allowing one to differentiate between the two snoring causes and decide on a more appropriate treatment strategy in each instance. Further investigations have concurred with this idea and claimed that it should indeed be possible to use sound spectral analysis to determine anatomically obstructive areas [5][6][7].…”
Section: Introductionmentioning
confidence: 97%